The Diagnostic Utility of Flow Cytometry in Celiac Disease Presented Isolated Iron Deficiency Anemia - Mete, Rafet; Oran, Mustafa; Altındağ Avcı, Burcu; Turgut, Burhan (Turkish Journal of Gastroenterology, 2021)
Background: Flow cytometric analysis of intestinal intraepithelial lymphocytes contributes to the diagnosis of celiac disease. Celiac disease may present with iron deficiency anemia alone which is considered as one of the forms of atypical celiac disease. In this study, we have aimed to investigate the diagnostic utility of flow cytometric analysis of intraepithelial lymphocytes in this atypical form. Methods: Three groups were formed: the patients with unexplained iron deficiency (group 1), the patients with celiac disease (group 2), and the patients who underwent gastroduodenoscopy for other reasons (group 0). Duodenal biopsy samples were used for flow cytometric analysis of intraepithelial lymphocytes. T cell receptor gammadelta intraepithelial lymphocytes and CD3−/CD103+ intraepithelial lymphocytes were determined with relevant monoclonal antibodies. Sensitivity–specificity calculation was performed to evaluate the usability of flow cytometric variables as diagnostic tests. Results: Group 1 had 22 patients, group 2 had 14 patients, and group 0 had 56 patients. In the comparison of the 3 groups, CD3+/ TCRγδ+ intraepithelial lymphocytes were found to be higher in celiac patients than other cases. CD3+/TCRγδ+ intraepithelial lymphocyte was evaluated for its usability as a diagnostic test. The cut-off value of CD3+/TCRγδ+ intraepithelial lymphocyte as 16.39% according to receiver operating characteristics curve analysis determined celiac disease in 14 of 22 patients in group 1 with 91.7% sensitivity and 80.4% specificity. Conclusions: Although celiac disease is diagnosed with serologic tests and histologic examination, successively, the increase in intestinal CD3+/TCRγδ+ intraepithelial lymphocytes may be used as a diagnostic test, and it may assist in revealing atypical forms of celiac disease.